Case Series of Lipid Accumulation in the Human Corpus Cavernosum. Issue 6 (February 2015) - Alwaal, Amjad; Wang, Lin; Zaid, Uwais B.; Lin, Guiting; Lue, Tom F.
Abstract : Abstract: Erectile dysfunction is a prevalent problem affecting millions of men in the United States and around the world. There have been no reports of the presence of lipids within the human penile corporal bodies, whether in normal or diseased states. We present here a case series of 9 patients who underwent penile corporal tissue biopsy during penile prosthesis insertion with severe intracorporal fibrosis and difficulties during insertion. Oil Red O staining was done to identify lipids; LipidTOX and phalloidin double staining was used to identify lipid location within the corpora, and Masson's trichrome staining was done to assess fibrosis. We identified lipid accumulation in those 9 corporal tissue samples, and further analysis showed the distribution to be 10% intramyocellular lipids and 90% extramyocellular lipids. These 9 specimens contained increased amount of collagen when compared with controls. In addition, we analyzed corporal samples from 10 random erectile dysfunction patients presenting for penile prosthesis insertion and identified no lipid accumulation in those control patients. This is the first report of lipid accumulation in the human corpus cavernosum. Possible mechanisms of lipid accumulation include androgen deficiency and dedifferentiation of corpus smooth muscle cells into other phenotypes; however, the exact mechanism is unknown and further research is needed.